ANALISA PERAWATAN INTAKE PUMP DENGAN MENGGUNAKAN METODE RISK BASED MAINTENANCE (RBM) - Ozkar F. Homzah; Ella Sundari; Rizky Brillian Yuliandi; Femi Permata Sari (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
Intake Pump is one of the important equipment in the steam power plant of 3x10 MW electrical generator which functions to supply raw water to production of demin water, domestic water and service water. In the process of producing water through the intake pump there are several components of the intake pump that often experience damage, this can be a loss for the company, therefore requiring additional processing. In this study, the Risk Based Maintenance (RBM) method was carried out to achieve optimal maintenance by knowing the impact and risk of failure according to important intake pump components, namely impeller, bearing and shaft. Based on the analysis results of the RBM calculation, the consequences of risks accepted is low to 0.05% by the company that achieved to 221,498,196.507 Indonesian rupiah it’s to 0.13% of production capacity per year. This value exceeds the acceptance risk tolerance of 0.13% which has become a company provision. Therefore, it is necessary to plan the proposed maintenance period from the existing policy, which is carried out 48 times a year for each critical component such to reducing the number of consequences and risks to 198,002,597 Indonesian Rupiah or equal to 0.01%.